HPLC analysis of in vivo metabolites of 4-nitrobenzoic acid [(5-nitro-2-thiopheneyl)methylenelhydrazide in rats - (:unkn) unknown (SPRINGER FRANCE, 2007)
The in vivo metabolism of 4-nitrobenzoic acid [(5-nitro-2-thiopheneyl)methylenelhydrazide (substrate), a model that represents hydrazide hydrazone compounds, was investigated in the rat. The metabolites were monitored in rat plasma at certain time intervals. The substrate was dissolved in dimethylsulfoxide (DMSO)/water (1:4) and administered intraperitoneally at dose of 100 mg/kg and 500 mg/kg. Blood samples were collected at 30 min, then at 1, 2, 4, 8, 12 and 24 h post-administration. The chromatographic separation of the substrate and its metabolites was performed on a Novapak C 18 (Phenomenex) (150 mm x 4.6 mm i.d., 5-mu m particle size) using a mobile phase consisting of phosphate buffer: acetonitrile (90: 10, v/v) with a linear gradient system. From the biotransformation of this compound, 4-nitrobenzoic acid (M3) was identified together with the substrate, as evidenced by high pressure liquid chromatography (HPLC)-UV/ diode array detection (DAD).
Keywords: hydrazone; in vivo metabolism; diode array detection; ANTIMYCOBACTERIAL ACTIVITY; ANTICONVULSANT ACTIVITY; ANTITUBERCULAR ACTIVITY; ANTIMICROBIAL ACTIVITY; ANTIFUNGAL ACTIVITY; HYDRAZONES; DERIVATIVES; VITRO; HYDRAZIDE